All-trans retinoic acid inhibits HOXA7 expression in leukemia cell NB4 - Guo, Q; Jiang, Q; Liu, W; Bai, Y (Cellular and Molecular Biology, 2016)
Leukemia is a malignant proliferative disease of blood system, which is caused by hyperplasia of white blood cells and infiltration into other tissues and organs with blood flow, leading to a series of clinical manifestations. In this study, we detected the expression of HOXA7 gene in human acute promyelocytic leukemia cell line NB4. The expression level of HOXA7 decreased in the presence of ATRA, which was able to inhibit the proliferation of NB4 cells. Furthermore, ATRA altered the morphology of NB4 cells. The study suggested that HOXA7 might be a new gene candidate that influences the maturation of acute myeloid leukemia, and provided the molecular basis for the treatment for acute promyelocyticleukemia.